Clean Water Initiative for Village Businesses (BUMDes) Development Betek Village, Krucil District, Probolinggo Regency, East Java - Pragusta, Reska; Girinada, Rizki Ganda (Universitas Tribhuwana Tunggadewi Malang, 2024)
The Betek area, Krucil District, Probolinggo Regency is at the foot of Mount Argopuro with deep groundwater conditions, so water in the ground is difficult to obtain. Currently, the need for clean water in Betek Village relies on spring sources around the area with a network simply built by the community. Unstable water source discharge is felt to be insufficient to meet community needs, especially during the dry season. So a study of underground water was carried out by approaching the electromagnetic field in the study area. One of the earth electromagnetic methods used is the magnetotelleuric method in the form of Audimomagnetotelleuric (ADMT) technology which can be used to determine the groundwater potential at the study location, where later the groundwater potential can be used to meet the community's water needs. The results of the ADMT track analysis on location show the continuity of groundwater potential on this path. Furthermore, an analysis of the ADMT path in the location B section shows the continuity of groundwater potential on the two tracks. At a depth of less than 40 meters, it is almost the same, while at a depth of more than 40 meters, it shows a different continuity. At a depth of less than 50 meters, it is almost the same, while at a depth of more than 60 meters, it shows a different continuity. If we look at the continuity of groundwater potential shown from ADMT-1 and ADMT-2, it shows that groundwater potential is dominant at 30 to 50 meters. So, from these two results, the selection of groundwater potential at ADMT-2 is 45 meters.